Product Market Competition, Returns to Skill and Wage Inequality - Maria Guadalupe (Institute for the Study of Labor (IZA), 2005)
This paper shows that increasing product market competition can have a direct impact on the employment relationship and on wage inequality. I develop a simple model in which an increase in product market competition increases returns to skill through the effect of competition on the sensitivity of profits to cost reductions. I then show empirically that relative wages increase with competition using a large panel of United Kingdom workers with complete work histories. I identify the impact of competition on returns to skill in the panel, using two exogenous measures of competition provided by two quasi-natural experiments. Quantile regressions indicate that increased competition also raised returns to unobserved ability.
Keywords: D21; L22; J33; J31; 330; wage structure; returns to skill; product market competition